2017
DOI: 10.3390/pharmaceutics9010009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of 20-Hydroxyeicosatetraenoic Acid in the Kidney, Liver, Lung and Brain: An Emerging Therapeutic Target

Abstract: Cytochrome P450-mediated metabolism of arachidonic acid (AA) is an important pathway for the formation of eicosanoids. The ω-hydroxylation of AA generates significant levels of 20-hydroxyeicosatetraenoic acid (20-HETE) in various tissues. In the current review, we discussed the role of 20-HETE in the kidney, liver, lung, and brain during physiological and pathophysiological states. Moreover, we discussed the role of 20-HETE in tumor formation, metabolic syndrome and diabetes. In the kidney, 20-HETE is involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 219 publications
(407 reference statements)
0
35
0
Order By: Relevance
“…64,123 These findings open up important diagnostic perspectives as regards directly estimating directly the balance between AA and the miscellanea of the other FFAs, for a direct, sensitive detection of their mobilization from cell membranes or storehouses as precursors of agents regulating harmful or protective responses to hazardous stimuli. [65][66][67][68][69][70][71] Possible applications include the monitoring of oxidative events in fatty livers relevant to the risk of progression to more severe liver and extrahepatic diseases. 67,68,[124][125][126][127][128][129] With regard to bilirubin, besides investigations on molecule photoisomerization to cure hyperbilirubinemia toxicity, 61,85,130 studies on its bichromophore properties have improved its diagnostic meaning in the bile.…”
Section: Op Ti C Al B I Opsy In Hepatologymentioning
confidence: 99%
See 2 more Smart Citations
“…64,123 These findings open up important diagnostic perspectives as regards directly estimating directly the balance between AA and the miscellanea of the other FFAs, for a direct, sensitive detection of their mobilization from cell membranes or storehouses as precursors of agents regulating harmful or protective responses to hazardous stimuli. [65][66][67][68][69][70][71] Possible applications include the monitoring of oxidative events in fatty livers relevant to the risk of progression to more severe liver and extrahepatic diseases. 67,68,[124][125][126][127][128][129] With regard to bilirubin, besides investigations on molecule photoisomerization to cure hyperbilirubinemia toxicity, 61,85,130 studies on its bichromophore properties have improved its diagnostic meaning in the bile.…”
Section: Op Ti C Al B I Opsy In Hepatologymentioning
confidence: 99%
“…The procedure was found to be efficient in differentiating between nonalcoholic fatty liver disease and chronic hepatitis, 142 at least in partial dependence on the release of components of the extracellular matrix into circulation from liver undergoing fibrosis. 143 Considering that fatty acids are recognized agents in sensing cell responses to hazardous stimuli, and that polyunsaturated fatty acids and their metabolites have been proposed as blood biomarkers of liver disease progression, [65][66][67][68][69][70][71]144 an additional diagnostic possibility is adapting the detection of the AF of free FFAs from liver tissue extracts to serum analysis, in a sort of liquid optical biopsy. 145…”
Section: Op Ti C Al B I Opsy In Hepatologymentioning
confidence: 99%
See 1 more Smart Citation
“…20-HETE was first characterized as a vasoactive eicosanoid that promotes vascular smooth muscle contraction, endothelial dysfunction, inflammation, and cell proliferation (10). These bioactions together with studies showing correlations between its levels in biological fluids, genetic variants of its synthetic enzymes and pathological conditions in humans and animal models are the basis for implicating 20-HETE in the development and the pathogenesis of disease and conditions, such as hypertension, stroke, myocardial infarction, kidney failure, and diabetes (4,42). With regard to obesity and diabetes, 20-HETE levels have been shown to increase in obese individuals and in animal models of obesity (18,31), and a study by Kim et al (20) showed that 20-HETE stimulates adipogenesis in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Among subterminal HETEs, 19-hydroxyeicosatetraenoic acid attracted the highest consideration as it represents the major cardiac subterminal HETE (El-Sherbeni and El-Kadi, 2014). 19-HETE acts as an endogenous antagonist of 20-HETE and inhibits its mediated vasoconstrictor effects (Elshenawy et al, 2017). Additionally, acute coronary syndrome patients with higher plasma levels of 19-HETE have significantly better prognosis than those who have lower plasma levels (Zu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%